Surgical Technique and Considerations about Transanal Transection and Single-Stapled (TTSS) Anastomosis: The Search for a Perfect Anastomosis - Campos, Fábio Guilherme; Pandini, Rafael Vaz; Bustamante-Lopez, Leonardo Alfonso; Nahas, Sérgio Carlos (Journal of Coloproctology, 2021)
The evaluation of preventive measures and risk factors for anastomotic leakage has been a constant concern among colorectal surgeons. In this context, the description of a new way to perform a colorectal, coloanal or ileoanal anastomosis, known as transanal transection and single-stapled (TTSS) anastomosis, deserves an appreciation of its qualities, and a discussion about its properties and technical details. In the present paper, the authors review the most recent efforts aiming to reduce anastomotic dehiscence, and describe the TTSS technique in a patient submitted to laparoscopic total proctocolectomy with ileal pouch-anal anastomosis for familial adenomatous polyposis. Surgical perception raises important advantages such as distal rectal transection under visualization, elimination of double-stapling lines (with cost-effectiveness and potential protection against suture dehiscence), elimination of dog ears, and the opportunity to be accomplished via a transanal approach after open, laparoscopic, or robotic colorectal resections. Future studies to confirm these supposed advantages are needed.
Keywords: colorectal anastomosis; rectal resection; single-stapled; transanal; transection